2021
DOI: 10.1515/dmdi-2021-0159
|View full text |Cite
|
Sign up to set email alerts
|

Study of the pharmacokinetics of various drugs under conditions of antiorthostatic hypokinesia and the pharmacokinetics of acetaminophen under long-term spaceflight conditions

Abstract: Objectives To study the pharmacokinetics and relative bioavailability of drugs of different chemical structure and pharmacological action under conditions simulating the effects of some factors of spaceflight, as well as the peculiarities of the pharmacokinetics of acetaminophen under long-term spaceflight conditions. Methods The pharmacokinetics of verapamil (n=8), propranolol (n=8), etacizine (n=9), furosemide (n=6), and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Based on these results, the authors concluded that encapsulated acetaminophen was preferred to the tablet form in space. A recent report largely confirmed the PK data obtained on the ISS, using the tablet formulation of acetaminophen (Kovachevich et al, 2009), in longer duration spaceflight (127–414 days) (Polyakov et al, 2021). This study was carried out applying a similar protocol, using saliva samples and included data from crewmembers that participated in space missions to the MIR orbital station.…”
Section: Drug Pk Studies In Space and In Surrogate Models Of Microgra...mentioning
confidence: 60%
See 4 more Smart Citations
“…Based on these results, the authors concluded that encapsulated acetaminophen was preferred to the tablet form in space. A recent report largely confirmed the PK data obtained on the ISS, using the tablet formulation of acetaminophen (Kovachevich et al, 2009), in longer duration spaceflight (127–414 days) (Polyakov et al, 2021). This study was carried out applying a similar protocol, using saliva samples and included data from crewmembers that participated in space missions to the MIR orbital station.…”
Section: Drug Pk Studies In Space and In Surrogate Models Of Microgra...mentioning
confidence: 60%
“…These data therefore suggest that the rate of drug absorption is increased during 6° HDT BR, in contrast to that observed using the HBR (Renwick et al, 1992; Rumble et al, 1991). The PK of acetaminophen was recently studied in a group of seven male subjects exposed to 2 days of 8° HDT BR (Polyakov et al, 2021). The study showed relevant differences in the profile of the averaged PK curves for acetaminophen among normal motion conditions (background) and 8° HDT BR.…”
Section: Drug Pk Studies In Space and In Surrogate Models Of Microgra...mentioning
confidence: 99%
See 3 more Smart Citations